THE APPLICATION OF ANALYTICAL HIERARCHY PROCESS (AHP)-MODIFICATION IN DETERMINATION OF LIVABILITY CITY INDEX (LCI) OF BANDUNG CITY - Suryo Nugroho, Bagoes
Analytical Hierarchy Process (AHP) is a model that uses mathematical principles to help decision makers determine the most logical decisions. One of the problems that can be solved using AHP by the Government of Bandung City is to determine the Livable City Index (LCI) of Bandung in 2017. The livable city describes an environment and a city atmosphere that is comfortable to be occupied by the community and as a place for activities which is seen from various aspects, both physical aspects (urban facilities, infrastructure, spatial planning, etc.) and non-physical aspects (social relations, economic activity, etc.). There are seven criteria that affect the livable city index of Bandung City, they are economy, transportation, spatial planning, utilities, social, environmental and health, also access to basic services. The weight calculation of the seven criterias will use the AHP-Modification method. The modification of the AHP method was carried out because the weighting rule criteria by Saaty(1987) involved an element of excessive subjectivity so that it could not produce an objective alternative solution in accordance with the objectives and problems that had been determined. The object to be modified is the weighting rule and pairwise comparison matrix. Based on descriptive statistics and value contour maps of each index or criterion that affects the LCI of Bandung City in 2017, it is known that the northern area of Bandung City, especially Cibeunying Kaler and Cibeunying Kidul Districts, are the districts with the highest LCI value. On the other hand, areas in the southern and suburbs of Bandung City have low LCI values. The sequence of weight value from each criteria that affects the Liveable City Index (LCI) of Bandung in 2017 based on its weight value are social (16,54%), environmental and health (16,31%), economic(14,67%), spatial (14,19%), utilities (14,19%), access to basic services (12,26%), and transportation criteria (11,95%). The consistency error value of applying the AHP-modified method is zero. In other words, this method produces consistent decision.